Performance of Concrete Using Burnt Waste Plastic as Partial Replacement for Coarse Aggregate - Samson Duna; Fwangmun B. Wamyil (Archives of Current Research International, 2017)
This study utilized plastic waste aggregate as partial replacement for coarse aggregate in concrete. The plastic was sourced from household and shop waste. It was sorted, cleaned, dried, burnt (openly), cooled and processed into average size of 20 mm while the physical properties were assessed. Concrete was produced using the burnt plastic waste as aggregate replacement at 10%, 20%, 50%, 60%, 80% and 100% by weight. A true slump with a maximum value of 23 mm was obtained at 10% plastic aggregate addition. Grade M25 concrete was produced and cured by water immersion for 3, 7, 14 and 28 day respectively. Assessment of water absorption, density and compressive strength were carried out. The result generally showed that the water absorption and density decreased with increase in plastic aggregate (PA) and curing period except for 50% and 60% plastic aggregate which showed a slight increase from 1.0% to 1.5 and 1.2% respectively from 3 day to 28 day curing. Similarly, the compressive strength decreased with increase in PA but there was increase in compressive strength along the days of curing. Concrete cubes made with (10-20) % plastic aggregates and cured for 28 days, achieved the 28 days target strength of 25 N/mm2. Regression and analysis of variance (ANOVA) in the MINITAB 16 statistical software was carried out on the research data. A model was developed to predict compressive strength with curing period and plastic aggregate content as predictors at 5% level of significance. The outcome showed a possibility for the replacement of coarse aggregate by plastic aggregate in concrete. The coefficients, R2 of 90.18% developed from the regression model is adequate for prediction of compressive strength.